Peranan Zakat dalam Pembangunan Ekonomi - Amie Amelia; Novia Nengsih (ZAWA: Management of Zakat and Waqf Journal, 2024)
Economics problems such as poverty and unemployment are still the main problems in Indonesia. Zakat as part of a redistributive instrument in Islamic economics is expected to be able to develop the economy and solve various economic problems. This research aims to examine the role of zakat in economic development. This research was library research. The results of this study explain that zakat can solve the problem of poverty, zakat can support a countryÔÇÖs economic growth, zakat can create economic policy, and zakat is an Islamic value system.